PENGARUH KOMPETENSI, SKEPTISISME PROFESIONAL, DAN ETIKA PROFESI AUDITOR TERHADAP KUALITAS AUDIT (SURVEY PADA KANTOR AKUNTAN PUBLIK DI KOTA MEDAN YANG TERDAFTAR PADA OJK) - Siagian, Dewi Asriyani; Rahmadhani, Sari Nuzullina (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study investigates the influence of auditor competence, professional skepticism, and professional ethics on audit quality among public accounting firms in Medan registered with the Financial Services Authority (OJK). Using a quantitative approach that combines descriptive and verification methods, the research collects data from 108 respondents representing auditors with varied educational and professional backgrounds. Multiple regression analysis reveals that each of the independent variables—auditor competence, professional skepticism, and professional ethics—has a significant positive impact on audit quality. In addition, the simultaneous influence of these factors explains a substantial proportion of the variability in audit quality. The findings underscore the importance of enhancing technical competencies, maintaining a critical mindset, and adhering to high ethical standards for improving the reliability and accountability of financial reporting. The study concludes with recommendations for auditors and regulatory bodies to further strengthen audit practices and bolster public trust in financial disclosures.